Falling in the Midst of Crisis: The Collapse of the Mangkunegaran Autonomous Government in the Social Revolution Era, 1945-1946 - Ramadhan, Fauzan Syahru; Alamsyah, Alamsyah; Rinardi, Haryono (Indonesian Historical Studies, 2023)
This article examines the social revolution in Surakarta, characterized by the anti-autonomous movement during the early years of the Indonesian Republic's independence, leading to the collapse of the Mangkunegaran autonomous government. Using historical methods, the article explores the initially positive relationship between the Mangkunegaran Duchy and the people in the late colonial period, evident in various factors such as support for education, economic initiatives, and infrastructure development. However, this relationship took a downturn during the social revolution due to external factors. Surakarta became a hub for radical movements, particularly the Anti-Autonomous movement, as the Mangkunegaran Duchy made unfortunate decisions. The study's goal is to uncover how the Mangkunegaran Autonomous Government navigated through the social revolution in Surakarta, even though it eventually collapsed. The study findings indicate that, facing a crisis after declaring independence, the Mangkunegaran Duchy made a critical error by betraying the Indonesian Republic and seeking to reinstate Dutch rule. In response, the people initiated a revolutionary movement. Ultimately, the Mangkunegaran Duchy failed to overcome the crisis, making misguided decisions and becoming victims of the revolution. They struggled to uphold the traditional politics and economy of the palace, which had endured for centuries and had been passed down through generations.